Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/epi.13888
|View full text |Cite
|
Sign up to set email alerts
|

Identifying psychogenic seizures through comorbidities and medication history

Abstract: Summary Objective Low-cost evidence-based tools are needed to facilitate the early identification of patients with possible psychogenic nonepileptic seizures (PNES). Prior to accurate diagnosis, patients with PNES do not receive interventions that address the cause of their seizures and therefore incur high medical costs and disability due to an uncontrolled seizure disorder. Both seizures and comorbidities may contribute to this high cost. Methods Based on data from 1,365 adult patients with video-electroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…9 Ammonia and lactate required narrow time windows (<1 hour, and 2 hours, respectively) to observe the changes. 13,14 Further studies of investigating the combination of the preceding methods and the concomitant AG and WBC cell biomarker changes for increasing the accuracy of determination of PNES vs ES would be interesting to pursue. Recent studies have shown that surface electromyography might help distinguish between convulsive PNES and ES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Ammonia and lactate required narrow time windows (<1 hour, and 2 hours, respectively) to observe the changes. 13,14 Further studies of investigating the combination of the preceding methods and the concomitant AG and WBC cell biomarker changes for increasing the accuracy of determination of PNES vs ES would be interesting to pursue. Recent studies have shown that surface electromyography might help distinguish between convulsive PNES and ES.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, a scoring system of clinical history and comorbidities has been proposed to diagnosis PNES, which achieved promising results. 13,14 Further studies of investigating the combination of the preceding methods and the concomitant AG and WBC cell biomarker changes for increasing the accuracy of determination of PNES vs ES would be interesting to pursue.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, seizure duration and frequency can provide valuable information in differentiating PNES from ES. Our mediocre accuracy and predictive values suggested that peri-ictal behaviors should be used in combination with other diagnostic information like comorbidities, medications, clinical history and neurodiagnostics [5,18,20,23,32,35,36]. For the diagnostic certainty to rise above "probable PNES," the patient's seizures need to be captured during EEG or directly observed directly by a clinician familiar with seizure disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our models may triage patients towards more definitive diagnostic testing. One theme observed in other diagnostic scores is that incorporating information about medical and psychiatric comorbidities as well as trauma history may increase the predictive performance [18,20,31,32]. Therefore, this evaluation should be considered in the appropriate clinical context.…”
Section: Individual-level Predictionsmentioning
confidence: 99%
See 1 more Smart Citation